2020
DOI: 10.1080/02783193.2019.1690081
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Autopsy of an Intellectually Gifted Student With Attention Deficit Disorder

Abstract: A psychological autopsy of an18-year-old male with dual exceptionalities contributes to our understanding of suicide among students with gifts and talents. Using four theories and models of suicide and research on the lived experience of students with gifts and talents, a comprehensive analysis of this adolescent's life offers implications for future suicide prevention among these students. Schools that are unprepared for exceptional students (gifted and/or 2e) may contribute to students' distress. Professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Without appropriate intervention, psychological problem among gifted students may become critical. A case of a psychological autopsy of a gifted 18-year-old male who suffered from depression decided to commit suicide is a melancholiest story explored by Cross et al (2020). Neihart and Yeo (2018) also found that gifted students are more at risk for psychological problems rather than normal students.…”
Section: Understanding the Nature Of Gifted Studentsmentioning
confidence: 99%
“…Without appropriate intervention, psychological problem among gifted students may become critical. A case of a psychological autopsy of a gifted 18-year-old male who suffered from depression decided to commit suicide is a melancholiest story explored by Cross et al (2020). Neihart and Yeo (2018) also found that gifted students are more at risk for psychological problems rather than normal students.…”
Section: Understanding the Nature Of Gifted Studentsmentioning
confidence: 99%
“…In addition, the participants emphasized the importance of practicing sports, artistic or creative activities for the self-regulation of stress, which could contribute to increasing their motivation and, consequently, achieving success in school. Cross et al (2020) conducted a psychological autopsy of a gifted young American with ADHD at the age of 18 to understand suicide among talented students. According to the authors, the psychological autopsy -a qualitative in-depth case study approach -was used to explore the participant's life and death trajectory based on different sources of information: school and health records, online conversations with the girlfriend, personal notes, and interviews with the mother, friends, family, teachers and school counselors.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, studies that investigated the relationship between giftedness, ADHD, and socio-emotional aspects indicated that gifted students with ADHD have lower scores on the self-esteem and selfconcept measures (Foley-Nicpon et al, 2012;Fugate & Gentry, 2016), which in some cases can result in aggressive behaviors and depressive symptoms, especially in adolescence and early adulthood (Cross et al, 2020;Fugate & Gentry, 2016). These individuals commonly face difficulties in regulating their emotions and are perceived in their interactions as immature, annoying, temperamental, or unpredictable, leading to a certain degree of social rejection by peers (Lovecky, 2004;Moon, 2002) and, consequently, interpersonal relationship difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by the World Health Organization (WHO, 2017), suicide ranks as one of the top three causes of adolescent death globally. There has been a growing research interest in gifted students, a uniquely vulnerable group at school, regarding their suicide cognitions, ideas, or behaviors (Cross & Cross, 2020; Cross et al., 2002; Cross et al., 2006; Cross et al., 2020; Martin et al., 2010). As discussed in previous research, three reasons that may increase the chance of gifted students’ suicidal behaviors are (a) the personality trait of perfectionism common to many gifted students, which could result in gifted students having very different perceptions of failure compared with other students (Apistola, 2017; Chan, 2010); (b) the societal expectations for the gifted students, which could be an additional source of external pressure for them, and could lead them to suicidal behaviors as well (Reis & McCoach, 2000); (c) the match between students’ giftedness and their development, which might not be in sync across social, emotional, or physical realms, thus, causing additional social and/or emotional distress (Pfeiffer & Stocking, 2000; Trujillo, 2018).…”
mentioning
confidence: 99%